Pengaruh Media Poster Terhadap Pemahaman Siswa Kelas 2 SD Muhammadiyah 07 Medan Denai - Mita Aprilia Lubis (Multidisciplinary Journal of Religion and Social Sciences, 2025)
This study aims to determine the extent to which poster media can enhance the understanding of second-grade students at SD Muhammadiyah 07 Medan Denai. The background of the research is based on the need for visual learning media that can attract students' attention and facilitate their comprehension of the material. This research uses a quantitative approach with a quasi-experimental method through a nonequivalent control group design. A total of 24 students were involved as research subjects, divided into two groups: experimental and control. The instrument used was an essay test consisting of five questions, administered during both the pre-test and post-test phases. The results show a significant improvement in students' understanding after the implementation of poster media. Before the treatment, only 8 students met the Minimum Mastery Criteria (KKM), whereas after the treatment, the number increased to 22 students. The average student score also rose from 48.5 in the pre-test to 79.4 in the post-test, with an average score difference of 30.9 points. Statistical analysis confirmed that this improvement was academically significant (p < 0.05). Thus, poster media proved to be effective in enhancing concept comprehension through engaging and communicative visual presentations, while also encouraging active student participation during the learning process.